The Factors FormÄ±ng Formal and Non Formal LeadershÄ±p Based on MÄ±nangkabau Culture in Padang - Sulastri, Sulastri; Andriani, Chichi; Fitria, Yuki (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
The purpose of this study is to establish and differentiate the concept and implementation of task function and task relation in Minangkabau leadership concept. This leadership concept implemented by three parties, namely, ninik mamak (clan leader), alim ulama (ecclesiastic)) and cerdik pandai (intellectual). This study collected data by survey questionnaire administered to formal and informal leaders in Padang, West Sumatra, Indonesia. The sample was 720 leaders selected through purposive sampling in 4 districts in Padang. The instrument in this study was developed based on Minangkabau alternative leadership and transformational leadership. Data were analyzed using discriminant analysis.